Assessing the hospital volume-outcome relationship in surgery: a scoping review protocol. Issue 10 (6th October 2020) - Levaillant, Mathieu; Marcilly, Romaric; Levaillant, Lucie; Vallet, Benoît; Lamer, Antoine
Abstract : Introduction: Even if a positive volume-outcome correlation in surgery is mostly admitted in many surgical fields, the various ways to assess this relationship make it difficult for researchers and policymakers to use it. Our aim is therefore to provide an overview of the way hospital volume-outcome relationship was assessed. Through this overview, our goal is to identify potential gaps in the assessment of this relationship, to help researchers who want to pursue work in this field and, ultimately, to help policy makers interpret such analyses. Methods and analysis: This review will be conducted using the six stages of the scoping review method: identifying the research question, searching for relevant studies, selecting studies, data extraction, collating, summarising and reporting the results and concluding. This review will address all the key questions used to assess the volume-outcome relationship in surgery. Primary research papers investigating the hospital volume-outcome relationship from 2009 will be included. Studies only looking at surgeons' volume-outcome relationship or studies were the volume variable is not individualisable will be excluded. Both MEDLINE and Scopus will be searched along with grey literature. Two researchers will perform all the stages of the review: screen the titles and abstracts, review the full text of selected articles to determine final inclusions and extract the data. The results will be summarised quantitatively using numerical counts. Ethical considerations and dissemination: Reviews of published articles are considered secondary analysis and do not need ethical approval. The findings will be disseminated through multiple channels like conferences and peer-reviewed journals.